(untitled) (Baghdad Science Journal, 2020)
coli K12 and B. subtilis 168 were investigated for their cadmium and mercury tolerance abilities. They were developed by UV mutagenesis technique to increase their tolerances either to cadmium or mercury, and their names then were designated depend on the name and concentration of metals. E. coli K12 Cd3R exhibited bioremediation amount of 6.5 mg Cd/g dry biomass cell. At the same time, its wild-type (E. coli K12 Cd3) was able to remove 5.2 mg Cd/g dry biomass cell in treatment of 17 mg Cd /L within 72 hours of incubation at 37 °C (pH=7) in vitro assays. The results show that E.coli K12 Hg 20 was able to remove 0.050 µg Hg/g dry biomass cell and more removal by its mutant E.coli K12 Hg 20R to 0.060 µg Hg/ g dry biomass cell in the treatment of 0.15 µg Hg /L. On the other hand, B. subtilis168 Cd2 was able to remove the least amount of cadmium (5 mg Cd/ g dry biomass cell) and of mercury (0.045 µg Hg/ g dry biomass cell) under the same conditions were used for E. coli K12. Also, the complete removal of both metals was confirmed by scanning electron microscopy (SEM) showing that the effect of cadmium and mercury on the bacterial mass. Also, the SEM images showed that the removal amounts had relationships in changing the morphology of cells under in vitroassays.